(untitled) (Open Academia: Journal of Scholarly Research, 2026)
This article presents an innovative pedagogical approach based on the integration of the Dominant Language Constellations (DLC) theory and foodways in teaching English to Uzbekspeaking learners. The study is fundamentally defined by the necessity to move away from traditional monolingual paradigms and link language learning with the student’s personal experience and cultural heritage. The article analyzes how culinary terminology, being closely intertwined with sensory and synesthetic memories (smell, taste, color), serves as a powerful tool for reinforcing vocabulary and creating emotional connections. The DLC framework allows learners to harmonize their native language and cultural identity with the process of acquiring English. Practical activities include menu analysis, simulation of culinary shows, and writing essays based on food memories. This methodology develops not only linguistic skills but also intercultural communicative competence and tolerance toward the concept of "otherness." The final conclusion emphasizes that integrating food culture into language education improves academic results while supporting the psychological well-being and personal development of students in a multilingual environment. For educators, this approach helps maximize students’ multilingual repertoires